Beyond a reasonable donut - Bolton, Ginger (Bolton, Ginger. Deputy Donut mystery., 2021)
"Selling her corn fritters at a carnival, Deputy Donut Café owner Emily Westhill faces off against a murderer who doesn't play fair"--